2016
DOI: 10.3928/01913913-20160113-03
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Four-Muscle Tenotomy Surgery for Nystagmus

Abstract: The authors have shown that four-muscle tenotomy surgery for nystagmus can improve VA and decrease nystagmus intensity. The study yielded subjective patient satisfaction, modest objective improvement in VA, and no significant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…[39] A study evaluating four-muscle tenotomy surgery for nystagmus has shown improvement in the visual acuity and decrease in the intensity of nystagmus. [40] A study by Singh et al . has evaluated the retroequatorial recession of horizontal rectus evaluation and Hertle-Dell'Osso procedure in patients with infantile nystagmus.…”
Section: Nystagmusmentioning
confidence: 99%
“…[39] A study evaluating four-muscle tenotomy surgery for nystagmus has shown improvement in the visual acuity and decrease in the intensity of nystagmus. [40] A study by Singh et al . has evaluated the retroequatorial recession of horizontal rectus evaluation and Hertle-Dell'Osso procedure in patients with infantile nystagmus.…”
Section: Nystagmusmentioning
confidence: 99%